2004
DOI: 10.1152/ajpheart.00784.2003
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of testosterone on intracellular Ca2+kinetics in rat coronary endothelial cells are exerted via aromatization to estrogens

Abstract: The objective of this work was to evaluate the effects of testosterone (T) and 17beta-estradiol (E(2)) on coronary microvascular endothelial cells (CMECs) of male and female rats. To analyze the short-term effects of such sex steroid hormones on intracellular Ca(2+) concentration ([Ca(2+)](i)) kinetics, we used the chelating agent fura-2 acetoxymethyl ester. We also explored the possibility of testosterone aromatization by using selective inhibitors of the aromatase enzyme cytochrome P-450 aromatase (P450(arom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 65 publications
(73 reference statements)
2
14
1
3
Order By: Relevance
“…Surprisingly, despite the observed sex difference in aromatase protein expression in cerebral vessels, we did not detect any sex differences in aromatase mRNA expression in microvascular endothelial cells. A lack of sex difference in aromatase expression has also been reported in rat coronary artery endothelial cells (50). Our data suggests that the sex difference in aromatase in cerebral vessels may be due to either increased expression in vascular smooth muscle cells from female mice or due to sex differences in post-transcriptional regulation of aromatase.…”
Section: Discussionsupporting
confidence: 73%
“…Surprisingly, despite the observed sex difference in aromatase protein expression in cerebral vessels, we did not detect any sex differences in aromatase mRNA expression in microvascular endothelial cells. A lack of sex difference in aromatase expression has also been reported in rat coronary artery endothelial cells (50). Our data suggests that the sex difference in aromatase in cerebral vessels may be due to either increased expression in vascular smooth muscle cells from female mice or due to sex differences in post-transcriptional regulation of aromatase.…”
Section: Discussionsupporting
confidence: 73%
“…The latter possibility is supported by investigations of other vascular systems, including prostacyclin production in endothelial cells (Mikkola et al 1995) and AT1 receptor gene expression in smooth muscle cells (Nickenig et al 1998), which have revealed that oestradiol may have a maximum effect at 12 h or greater. Endothelial cells can convert testosterone to oestradiol (Mukherjee et al 2002) and it has been suggested that effects attributed to testosterone may be in part a result of its conversion to oestradiol (Sierra-Ramirez et al 2004). However, our observation that testosterone increased the number of adrenomedullin-secreting endothelial cells, and that oestradiol had no significant effect, indicates that the actions of testosterone exhibited here were unlikely to be dependent on its conversion to oestradiol.…”
Section: Discussioncontrasting
confidence: 58%
“…For example, both vasodilatory (Webb et al 1999) and anti-vasodilatory effects have been observed (Hutchison et al 1997, Ceballos et al 1999 and testosterone may be involved in the development of some forms of experimental hypertension (Song et al 2004, Reckelhoff 2005. Endothelial cells have receptors for both oestradiol (Losordo et al 1994) and testosterone (Sierra-Ramirez et al 2004), by which these steroids can directly influence blood vessels and hence the development of vascular disease and hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…This may be because of the availability of more membrane AR than ER in HUVECs. Although the existence of membrane ER and AR has been reported in various cell types, including ECs, in several studies (Armen and Gay 2000;Rubio-Gayosso et al 2002;Sierra-Ramirez et al 2004;Kampa et al 2005), none of them have analyzed ER and AR. However, in agreement in principle with our results, AR is expressed at higher levels than ER and the progesterone receptor in the ECs of the oral mucosa (Ojanotko-Harri et al 1992).…”
Section: Discussionmentioning
confidence: 99%